FAMILY COMMUNICATION EXPERIENCES OF GEN Z WITH NEGATIVE INNER CHILD IN RELATION TO THE QUARTER-LIFE CRISIS PHASE - Adisti, Syavira; Rozi, Fakhrur (Journal Analytica Islamica, 2025)
Family communication serves as the fundamental basis for character development and emotional well-being. Unhealthy family communication—such as being closed-off, overly critical, or lacking in validation—poses a risk of forming a negative inner child. A negative inner child refers to adverse childhood experiences that impact an individual's emotional life in adulthood. Gen Z, a generation raised during the digital era and under intense social pressures, often carries negative inner child experiences from childhood, which influence their adult lives. These emotional wounds may lead to difficulties in emotional regulation, establishing healthy relationships, and coping with life challenges—especially during the quarter-life crisis phase, a period of identity crisis typically occurring between the ages of 20 and 30, marked by anxiety due to social pressure and confusion in determining life direction and purpose.This study aims to analyze and understand the subjective experiences of Gen Z individuals with negative inner child in the context of the quarter-life crisis, particularly how emotional wounds from unhealthy family communication during childhood contribute to patterns of thinking, communication, and decision-making in adulthood. This research employs a phenomenological approach, involving in-depth interviews with three Gen Z participants aged 20–30 who have experienced a negative inner child. The findings indicate that Gen Z individuals with negative inner child experiences and authoritarian, affectionless, or pressure-filled family communication tend to suffer from identity confusion and a lack of direction in determining life goals. This study emphasizes the importance of healthy family communication in fostering emotional resilience and adaptive capacity among Gen Z as they face their future lives.